2022
DOI: 10.1007/s00464-022-09601-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of laparoscopic common bile duct exploration with primary closure and intraoperative endoscopic nasobiliary drainage for choledocholithiasis combined with cholecystolithiasis

Abstract: Background The need for intraoperative endoscopic nasobiliary drainage during laparoscopic cholecystectomy and laparoscopic common bile duct exploration with primary closure is controversial in the treatment of cholecystolithiasis combined with choledocholithiasis. The aim of this study was to evaluate the safety and efficacy of laparoscopic cholecystectomy + laparoscopic common bile duct exploration + intraoperative endoscopic nasobiliary drainage + primary closure (LC + LCBDE + IO-ENBD + PC). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…The included investigations compared the laparoscopic common bile duct exploration combined (LCBDE) to the laparoscopic cholecystectomy (LC) combined with intraoperative endoscopic sphincterotomy (IOEST). The success rates in both interventions were similar; however, only two studies reported that LCBDE had higher success rates than LC-IOEST (ElGeidie et al, 2011b;Zhang et al, 2022). Most studies reported more complications in the LC-IOEST except for two investigations (González et al, 2016;Zhang et al, 2022).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 88%
See 3 more Smart Citations
“…The included investigations compared the laparoscopic common bile duct exploration combined (LCBDE) to the laparoscopic cholecystectomy (LC) combined with intraoperative endoscopic sphincterotomy (IOEST). The success rates in both interventions were similar; however, only two studies reported that LCBDE had higher success rates than LC-IOEST (ElGeidie et al, 2011b;Zhang et al, 2022). Most studies reported more complications in the LC-IOEST except for two investigations (González et al, 2016;Zhang et al, 2022).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 88%
“…The success rates in both interventions were similar; however, only two studies reported that LCBDE had higher success rates than LC-IOEST (ElGeidie et al, 2011b;Zhang et al, 2022). Most studies reported more complications in the LC-IOEST except for two investigations (González et al, 2016;Zhang et al, 2022). The LC-IOEST was found to reduce the duration of posthospital stay, except for one study reported by ElGeidie et al (2011b).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 90%
See 2 more Smart Citations
“…LCBDE is a common surgical method for the treatment of gallstones and CBD stones, but about 15% of patients with T-tube drainage will have complications such as water and sodium electrolyte disorders, biliary peritonitis after T-tube removal, and T-tube displacement [17][18][19] . At present, the literature is more and more inclined to primary suture [20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%